The Influence of Company Characteristics on Firm Value: Evidence from Indonesian Property and Real Estate Companies - Rika Desiyanti (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2026)
This study analyzes the influence of capital structure, business size, and sales growth on firm value among property and real estate companies listed on the Indonesia Stock Exchange over the 2020–2025 timeframe. The study was prompted by oscillations in the performance of the Indonesian property industry and conflicting conclusions published in earlier empirical studies about the determinants of business value in emerging economies. A quantitative explanatory technique was applied, employing secondary data from the annual financial reports of listed corporations. The sample was selected via census sampling. The findings reveal that corporate factors, particularly capital structure, sales growth, and firm size, have a crucial influence in shaping firm value. The results imply that funding and growth decisions contribute greatly to investor views and market valuation. These findings give practical implications for managers in identifying optimal financial strategies and for investors in evaluating business performance within the property and real estate industry.